KONSEP PENDIDIKAN ISLAM DALAM PENANGGANAN KORUPSI - Yayan Ridwan (Cross-border, 2022)
Today the world's leaders and politicians are no longer able to bring peace to the world. It seems the only hope lies in education. In this century, many educational experts have produced many new theories. However, education has failed to bring peace in the world. It is not the fault of the educators and students, but it can be seen that education is often directed by politics and the economy. Through these many bitter lessons, many have begun to realize that education should not only produce great people but must also produce good people. It is clear that if we have people who are smart but only selfish or people with high intellectual abilities but without moral character so that they are prone to corruption then our country will not be peaceful and prosperous. Islamic values ​​are needed in the world of politics, homes, businesses, factories and offices, schools, to this country that we have. Basically, Islamic values ​​exist in all of us and in all aspects of life. It is not violence and selfishness that we need, but love and compassion in the human heart. I think the most appropriate solution to overcome this problem is to return to human education to become a better human being; education based on the one and only God, which is more appropriate, is Islamic education and Pancasila.